Incentive Contracts and Hedge Fund Management: A Numerical Evaluation Procedure - Jens Carsten Jackwerth; James E. Hodder (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
The behavior of a hedge-fund manager naturally depends on her compensation scheme, her preferences, and constraints on her risk-taking. We propose a numerical method which can be used to analyze the impact of these influences. The model leads to several interesting and novel results concerning her risk-taking and other managerial decisions. We are able to relate our results to partial results in the literature and show how they fit in a more general context. We also allow the manager to voluntarily shutdown the fund as well as enhancing the fund's Sharpe Ratio through additional effort. Both these extensions generate additional insights. Throughout the paper, we find that even slight changes in the compensation structure or the extent of managerial discretion can lead to drastic changes in her risk-taking.
urn:nbn:de:bsz:352-opus-11718
Keywords: 330; Investmentfonds; Hedging; Anlageverhalten; Führungskräfte; Vergütungssystem; Anreizvertrag; Theorie